Abscisic acid-induced resistance against the brown spot pathogen Cochliobolus miyabeanus in rice involves MAP kinase-mediated repression of ethylene signaling - De Vleesschauwer, David; Yang, Yinong; Vera Cruz, Casiana; Höfte, Monica (Oxford University Press, 2010)
The plant hormone abscisic acid (ABA) is involved in an array of plant processes, including the regulation of gene expression during adaptive responses to various environmental cues. Apart from its well-established role in abiotic stress adaptation, emerging evidence indicates that ABA is also prominently involved in the regulation and integration of pathogen defense responses. Here, we demonstrate that exogenously administered ABA enhances basal resistance of rice (Oryza sativa) against the brown spot-causing ascomycete Cochliobolus miyabeanus. Microscopic analysis of early infection events in control and ABA-treated plants revealed that this ABA-inducible resistance (ABA-IR) is based on restriction of fungal progression in the mesophyll. We also show that ABA-IR does not rely on boosted expression of salicylic acid-, jasmonic acid -, or callose-dependent resistance mechanisms but, instead, requires a functional Gα-protein. In addition, several lines of evidence are presented suggesting that ABA steers its positive effect on brown spot resistance through antagonistic cross talk with the ethylene (ET) response pathway. Exogenous ethephon application enhances susceptibility, whereas genetic disruption of ET signaling renders plants less vulnerable to C. miyabeanus attack, thereby inducing a level of resistance similar to that observed on ABA-treated wild-type plants. Moreover, ABA treatment alleviates C. miyabeanus-induced activation of the ET reporter gene EBP89, while derepression of pathogen-triggered EBP89 transcription via RNA interference-mediated knockdown of OsMPK5, an ABA-primed mitogen-activated protein kinase gene, compromises ABA-IR. Collectively, these data favor a model whereby exogenous ABA enhances resistance against C. miyabeanus at least in part by suppressing pathogen-induced ET action in an OsMPK5-dependent manner.